Analysis of the Influence Instagram Marketing Activities on Customer Based Brand Equity of the Local Skincare Brand Avoskin Beauty - Mahendra, Mahesh; Fadhilla, Hanifa Nur (MEC-J (Management and Economics Journal), 2025)
The research aims to test and analyze the influence of Instagram marketing activities on customer-based brand equity (brand awareness, brand image, perceived quality, brand love, and Instagram brand re-usage intention). The population in this research is the young generation of productive age in Yogyakarta, and used products from the Avoskin brand. This research uses quantitative methods, the sampling technique is purposive sampling and the data analysis technique uses partial least squares (PLS-SEM) then processed using the SmartPLS 3.0 program. The results of the research show that Instagram marketing activities have a positive effect on brand equity (brand awareness, brand image and perceived quality), while brand equity (brand awareness, brand image and perceived quality) has a positive effect on brand love and Instagram brand re-usage intention. These findings provide actionable insights for businesses aiming to leverage Instagram as a strategic marketing platform. Companies can strengthen customer loyalty and drive sustainable growth by focusing on enhancing brand visibility, improving perceived quality, and fostering emotional connections with consumers through targeted Instagram campaigns.